The Influence of Work and Personal Life Interference and Emotional Exhaustion on Counterproductive Work Behavior - Syahroni Syahroni; Abdul Haeba Ramli (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Conflicts between personal life and work are increasingly common due to dynamic work environments and growing job demands. This study aims to analyze the effects of Work Interference With Personal Life (WIPL), Personal Life Interference With Work (PLIW), and Emotional Exhaustion on Counterproductive Behavior (CPB) among employees at poultry slaughterhouses. A quantitative approach was employed through a questionnaire survey distributed to 196 respondents. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 4 software. The results reveal that WIPL does not significantly affect CPB, while both PLIW and Emotional Exhaustion have a positive effect on CPB. Moreover, WIPL and PLIW significantly increase Emotional Exhaustion levels. However, Emotional Exhaustion does not mediate the relationship between WIPL or PLIW and CPB. These findings highlight the importance of managing emotional fatigue and ensuring work-life balance to prevent counterproductive behaviors in the workplace. Keywords: Work Interference With Personal Life, Personal Life Interference With Work, Emotional Exhaustion, Counterproductive Behavior